Pengaruh Budaya Organisasi terhadap Kinerja Pegawai melalui Kepuasan Kerja pada Kantor Dinas Lingkungan Hidup Kebersihan dan Keindahan Kota Banda Aceh - Aldika Maulizi Effendi; Agus Ariyanto; Febyolla Presilawati (Jurnal Manajemen Riset Inovasi, 2026)
This study aims to analyze the influence of organizational culture on employee performance through job satisfaction at the Banda Aceh City Environmental, Sanitation, and Beautification Office. This study employs a quantitative approach using an associative method. The study population consisted of 44 civil servants, all of whom were included in the sample using a census method. Data collection was conducted via a questionnaire using a Likert scale, supplemented by observations and interviews. The data analysis techniques employed included path analysis, t-tests, the coefficient of determination (R²), and the Sobel test to examine the mediating role. The results of the study indicate that organizational culture has a positive and significant effect on employee performance, with a significance value of 0.004 and a calculated t-value of 3.014. Organizational culture also has a positive and significant effect on job satisfaction, with a p-value of 0.003 and a t-statistic of 3.940. Furthermore, job satisfaction has a positive and significant effect on employee performance with a significance value of 0.000 and a t-value of 5.174. A mediation test using the Sobel test indicates that job satisfaction significantly mediates the effect of organizational culture on employee performance with a t-value of 3.818 (>1.96). The coefficient of determination of 0.832 indicates that 83.2% of the variation in employee performance can be explained by organizational culture, job satisfaction, and their interaction, while the remainder is influenced by other variables outside the scope of this study. Thus, it can be concluded that organizational culture has a strong influence on improving employee performance, both directly and through job satisfaction as a mediating variable.